Infections, autoimmunity and immunodeficiencies are the leading etiologies of non-cystic fibrosis bronchiectasis in adults from the southwest of Colombia. - Andrés F. Zea-Vera; Carlos Andrés Rodríguez; Sebastián Giraldo; Mario Alejandro Chacón; Luis Fernando Guerrero; Ricardo Mosquera; Raúl Andrés Vallejo; Fabio Samir Vargas; María Andrea García; María A. Rengifo; Anilza Bonelo; Maximiliano Parra (Biomédica: revista del Instituto Nacional de Salud)
Introduction. Non-cystic fibrosis bronchiectasis is a complex medical condition with multiple etiologies, characterized by chronic productive cough and radiologic evidence of airway lumen dilation and wall thickening. Associated exacerbations and declining lung function contribute to increasing disability and mortality. There are no data about the prevalence of non-cystic fibrosis bronchiectasis etiologies in the Colombian population. Objective. To investigate non-cystic fibrosis bronchiectasis etiology and clinical characteristics in adults evaluated in the southwest of Colombia. Materials and methods. We conducted a cross-sectional, non-interventional study. Subjects diagnosed with non-cystic fibrosis bronchiectasis were referred to by their healthcare providers and then enrolled between October 2018 and April 2021. Medical records and radiological studies were evaluated. Participants underwent laboratory tests, including complete blood count, serum immunoglobulin levels, and, in some cases, additional tests. Results. We included 161 subjects. The average age was 50 years old, and 59% were females. Bronchiectasis etiology was identified in 84.6% of the cases. Postinfectious (34.6%) and immune disorders (25.3%), represented by autoimmunity (13.6%) and immunodeficiency (11.7%), were the leading causes. Gender differences were noted in autoimmune (females: 18.8% versus males: 6.1%, p = 0.021) and immunodeficiency-related bronchiectasis (males: 21.2% versus females 5.2%, p = 0.002). Immunodeficiencies-associated bronchiectases were more frequent in subjects under 50 years of age, while chronic obstructive pulmonary disease-associated bronchiectases were common in subjects over 50 years of age. Discussion. The etiologies of non-cystic fibrosis bronchiectasis in Colombia are diverse, exhibiting notable differences from other global regions. Serum immunoglobulin levels and clinical immunologist consultation should be prioritized in diagnosing patients with unclear bronchiectasis etiology, particularly those with recurrent sinopulmonary infections.